2019
DOI: 10.1002/jbm.a.36727
|View full text |Cite
|
Sign up to set email alerts
|

Regional gene therapy with 3D printed scaffolds to heal critical sized bone defects in a rat model

Abstract: The objective of the present study was to assess the ability of transduced rat bone marrow cells (RBMCs) that overexpress BMP-2 loaded on a three-dimensionally (3D) printed scaffold to heal a critical sized rat femoral defect. Tricalcium phosphate (TCP) scaffolds were 3D printed to fit a critical sized rat femoral defect. The RBMCs were transduced with a lentiviral (LV) vector expressing BMP-2 or GFP. The rats were randomized into the following treatment groups: (1) RBMC/LV-BMP-2 + TCP,(2) RBMC/LV-GFP + TCP, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…Indeed, Blum et al compared the osteogenic effects of adenoviral vectors and retroviruses for BMP-2 gene delivery, and adenoviral vectors were superior to retroviruses in terms of osteogenic differentiation and bone formation [68]. As a result, lentiviral BMP-2 gene delivery is utilized for the investigation of characteristics related to BMP-2 in bone healing or the development of innovative strategies for BMP-2 gene therapy [49,50,69,70,71]. Alaee et al suggested dual expression of a suicide gene and BMP-2 gene in a lentiviral vector due to safety concerns [72].…”
Section: Bmp-2 Gene Deliverymentioning
confidence: 99%
“…Indeed, Blum et al compared the osteogenic effects of adenoviral vectors and retroviruses for BMP-2 gene delivery, and adenoviral vectors were superior to retroviruses in terms of osteogenic differentiation and bone formation [68]. As a result, lentiviral BMP-2 gene delivery is utilized for the investigation of characteristics related to BMP-2 in bone healing or the development of innovative strategies for BMP-2 gene therapy [49,50,69,70,71]. Alaee et al suggested dual expression of a suicide gene and BMP-2 gene in a lentiviral vector due to safety concerns [72].…”
Section: Bmp-2 Gene Deliverymentioning
confidence: 99%
“…Researchers have attempted the reconstruction of critical‐size segmental defects in rat femurs using various scaffolds 9,15,18,23 . Kim et al 9 reported that very little bone had formed in the proximity of segment ends of native bone at 4 weeks post‐implantation when chitosan‐lactide‐fibrinogen hydrogel scaffolds alone were implanted into the segmental bone defects of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 9 reported that very little bone had formed in the proximity of segment ends of native bone at 4 weeks post‐implantation when chitosan‐lactide‐fibrinogen hydrogel scaffolds alone were implanted into the segmental bone defects of rats. Alluri et al 18 reported that when TCP scaffolds alone were implanted into the segmental bone defects of rats, little bone formed at the scaffold–defect interface and no bone had formed surrounding the scaffold, even at 12 weeks post‐implantation. Furthermore, even combined scaffolds and bone morphogenetic protein‐2 (BMP‐2) did not achieve complete recovery at 8 weeks post‐implantation, and 12 weeks were needed for complete recovery 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The narrow range of current treatment choices has generated a marked interest in improving translational bone regeneration policies to repair bone defects safely and effectively. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%